Está en la página 1de 1

1- Hallar x en log(𝑥 2 + 3𝑥 + 12) = 2

log(𝑥 2 + 3𝑥 + 12) = 2
102 = 𝑥 2 + 3𝑥 + 12
100 = 𝑥 2 + 3𝑥 + 12
𝑥 2 + 3𝑥 − 88 = 0
(𝑥 + 11)(𝑥 − 8) = 0
𝑥 = −11
𝒙=𝟖
2- Hallar x en log √2 32 = 𝑥
log √2 32 = 𝑥
𝑥
√2 = 32
𝑥
2 2 = 25
𝑥
=5
2
𝒙 = 𝟏𝟎
3- Hallar x en 2 log 𝑥 = log(6𝑥 + 7)

2 log 𝑥 = log(6𝑥 + 7)
log 𝑥 2 = log(6𝑥 + 7)
𝑥 2 = 6𝑥 + 7
𝑥 2 − 6𝑥 − 7 = 0
(𝑥 − 7)(𝑥 + 1) = 0
𝑥 = −1
𝒙=𝟕
4- Hallar x en log(𝑥 + 10) − log(2𝑥 + 5) = log(𝑥 − 4)
log(𝑥 + 10) − log(2𝑥 + 5) = log(𝑥 − 4)
(𝑥 + 10)
log = log(𝑥 − 4)
(2𝑥 + 5)
(𝑥 + 10)
= (𝑥 − 4)
(2𝑥 + 5)
(𝑥 + 10) = (2𝑥 + 5)(𝑥 − 4)
𝑥 + 10 = 2𝑥 2 + 5𝑥 − 8𝑥 − 20
0 = 2𝑥 2 − 4𝑥 − 30
0 = 𝑥 2 − 2𝑥 − 15
(𝑥 − 5)(𝑥 + 3) = 0
𝑥 =-3
𝒙=𝟓

5- Hallar x en 𝑥 = log 2 2√2


𝑥 = log 2 2√2
1
𝑥 = log 2 2 ∗ 22
3
𝑥 = log 2 ∗ 22
𝟑
𝒙=
𝟐